Exploring Bias in Student Evaluations: Gender, Race, and Ethnicity - Chávez, Kerry; Mitchell, Kristina M.W. (PS, political science & politics, 2020)
Research continues to accumulate showing that in instructor evaluations students are biased against women. This article extends these analyses by examining the dynamics between evaluations and gender and race/ethnicity. In a quasi-experimental design, faculty members teaching identical online courses recorded welcome videos that were presented to students at the course onset, constituting the sole exposure to perceived gender and race/ethnicity. This enables exploration of whether and to what degree the instructors’ characteristics influenced student evaluations, even after holding all other course factors constant. Findings show that instructors who are female and persons of color receive lower scores on ordinal student evaluations than those who are white males. Overall, we add further evidence to a growing literature calling for student evaluations of teaching (SETs) reform and extend it to encompass the effects on racial/ethnic minorities in addition to women.